Perencanaan Pembelajaran dan Pengaruhnya Terhadap Kompetensi Guru Pendidikan Agama Hindu - I PUTU WIDYANTO (Lembaga Penelitian dan Pengabdian pada Masyarakat Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2020)
Learning planning is a set of plans and arrangements for learning activities, which contain objectives, materials, learning tools and infrastructure, approaches, strategies or evaluation of results and learning processes used as guidelines in learning on the achievement of learning objectives. Learning planning can provide benefits including facilitating the preparation of learning and facilitating the development of active, creative, effective and enjoyable learning so that it will improve teacher competence. The purpose of this study was to analyze how the implementation of learning planning affects the competence of Hindu religious education teachers. This study uses a qualitative research approach to the type of library research (Library Research). The results of the study show that learning planning is very important for the course of learning because it is a guide for teachers in implementing learning because with good learning planning will implement learning run well that will have an impact on increasing four teacher competencies including pedagogical competence, personality competence, social competence, and professional competence.